Hubungan Pengetahuan, Sikap dan Intensi Perilaku Pengelolaan Sampah Berkelanjutan Pada Siswa Sekolah Dasar di Kota Padang - Aria Gusti; B Isyandi; Syaiful Bahri; Dedi Afandi (Universitas Riau, 2015)
This studi examined the behavioral intention of sustainable waste management inelementary school student using the framework of Theory of Planned Behavior. The objectiveof this study was to know the relationship of knowledge, attitude, and the behavioral intentionof sustainable waste management. Population and sample in this study were elementaryschool students in the Padang City, West Sumatra. The data collected for this study wereanalyzed using Structural Equation Modeling (SEM). The results of this study stated that theknowledge about sustainable waste management has a significant relationship with attitudestowards sustainable waste management. Knowledge and attitudes towards sustainable wastemanagement had a significant association with the behavioral intention of sustainable wastemanagement. These findings have important implications for the school as well as for policymakers.